OCTA / Europol / 2008 (OCTA EU organised crime threat assessment, 2008)
In response to ‘The Hague Programme’, the first OCTA was introduced and later endorsed by the Council during their meeting on 1-2 June 2006. The OCTA, and the ensuing Council Conclusions based on the OCTA from 2006 and 2007, have already had a significant impact on law enforcement work throughout Europe. This third OCTA will provide an important platform for the evaluation of the Council Conclusions of 2006 and 2007. The OCTA covers the EU. However, it cannot be neglected that Europe, due to its geography and its cultural, social and historical differences, is not a homogeneous structure and so may also require a regional priority setting. Therefore, although the European dimension is the prime focus, the OCTA also accounts for regional divergences. In order to enhance the understanding of events within the EU, consideration of the international arena is at times necessary. To support decision-makers in the best possible way, the OCTA provides a well-targeted qualitative assessment of the threat from OC. The OCTA is based on a multi-source approach, including law enforcement and non-law enforcement contributions. These include various European agencies as well as the private sector. A specific emphasis is put on elaborating the benefits of an intensified public-private partnership. The OCTA helps to close the gap between strategic findings and operational activities. The OCTA helps to identify the highest priorities, which will then be effectively tackled with the appropriate law enforcement instruments. The OCTA suggests strategic priorities, but it needs to be realised that the OCTA itself is not detailed enough to pinpoint specific criminal investigations. The structure of the 2008 OCTA follows the general conceptual model for the analysis, starting with an assessment of the OC groups, followed by an analysis of the criminal markets and ending with an assessment of the regional dimension of OC impacting on the EU. The OCTA is always being enhanced. Methodological and other issues are continuously being addressed in close cooperation with the Member States to allow for the further enhancement of the OCTA. The methodology and procedures for its completion have been amended. Overall, the changes which have been introduced have all contributed to enhancing the quality of the OCTA. The OCTA does not cover terrorism or terrorist networks.